Regulation of superoxide dismutase synthesis in Escherichia coli: glucose effect. - Moustafa Hassan, H (1977)
Growth of Escherichia coli, based upon the fermentation of glucose, is associated with a low intracellular level of superoxide dismutase. Exhaustion of glucose, or depression of the pH due to accumulation of organic acids, causes these organisms to then obtain energy from the oxidative degradation of other substances present in a rich medium. This shift in metabolism is associated with a marked increase in the rate of synthesis of superoxide dismutase. Depression of the synthesis of superoxide dismutase by glucose is not due to catabolite repression since it is not eliminated by cyclic adenosine 3',5'-monophosphate and since alpha-methyl glucoside does not mimic the effect of glucose. Moreover, glucose itself no longer depresses superoxide dismutase synthesis when the pH has fallen low enough to cause a shift to a non-fermentative metabolism. It appears likely that superoxide dismutase is controlled directly or indirectly by the intracellular level of O2- and that glucose depressed the level of this enzyme because glucose metabolism is not associated with as rapid a production of O2- as is the metabolsim of many other substances. In accord with this view is the observation that paraquat, which can increase the rate of production of O2- by redox cycling, caused a rapid and marked increase in superoxide dismutase.